Willingness to pay to avoid flooding in Cuttack, India. (1st February 2021) - Mahaprashasta, Jogasankar; Mukhopadhyay, Pranab; Pattanayak, Subhrendu K.
Abstract: Flooding is a frequent natural disaster, which is predicted to intensify over time because of climate change. As more than half the world lives in urban spaces, flooding could devastate urban populations, especially if the infrastructure to cope with flooding is inadequate. We study flooding in Cuttack, Odisha, a typical Indian city subject to annual flooding. We present estimates from a lower and lower-middle income country of household willingness to pay (WTP) for improved urban drainage using a revealed preference method. We use a hedonic price model to estimate WTP across city zones with differential exposure to flooding. At 2014–15 prices, a typical flood (approximately 7 hours per day on average) reduces the annual rental value by INR1352 (US 21) or about 4.4% annually. This implies that Cuttack households are willing to pay INR 188 million (or 2.9 million) to avoid flooding. Our findings have implications for urban sustainability and the financing of public infrastructure to reduce flooding in low and lower-middle-income countries.